O3A.6 Recent organic dust exposure and prognosis of asthma and chronic obstructive lung disease (COPD). A nationwide register based follow-up study. (April 2019) - Vested, Anne; Basinas, Ioannis; Burdorf, Alex; Elholm, Grethe; Heederik, Dick; Jacobsen, Gitte; Kolstad, Henrik; Kromhout, Hans; Omland, Øyvind; Sigsgaard, Torben; Vestergaard, Jesper Medom; Wouters, Inge; et al.
Abstract : Background: Air pollutants at work can contribute to onset of asthma and COPD. How occupational air pollutants affect the prognosis of asthma or COPD among exposed workers is not well established. Objective: We aimed, among individuals with a hospital diagnosis of asthma or COPD, to study the association between recent exposure to organic dust, and hospital readmission and overall mortality. Methods: The study population comprised individuals ever employed in farming or wood industry with asthma (n=4002) or COPD (n=2429) identified in the Danish national patient register of individuals born 1933–1977. Subjects were included the year immediately following their first asthma or COPD hospital contact (earliest in 1998) and followed until first asthma or COPD readmission, death, or December 31 st 2007. Exposure data was obtained through register-based industry codes from 1997–2007 combined with time-dependent farming and wood industry-specific exposure matrices. We used logistic regression analysis with discrete survival function adjusted for age, calendar year, sex, mineral dust exposure, socioeconomic status, and labour-force participation. Results: Among individuals with asthma, the risk of hospital readmission was slightly increased among the exposed vs. the non-exposed, RRadj 1.17 (0.91–1.50), but with no exposure trend. A non-significant decrease in mortality was seen for organic dust exposure and mortality for those individuals, RRadj 0.71 (0.24–2.06). The risk of a COPD readmission among individuals with COPD was decreased among exposed vs. non-exposed individuals, RRadj 0.67 (0.46–0.98), but with no exposure trend. Mortality was non-significantly increased for exposed vs. non-exposed individuals with COPD, RRadj 1.59 (0.82–3.08). Conclusion: We did not observe significant associations between recent exposure to organic dust and readmission for COPD/asthma or overall mortality except for a decreased risk for COPD readmission. Selection effects are presumably playing a role. We did adjust for socioeconomic position and labour-force participation but not for smoking which is a limitation.